At a General Assembly of the governor and company of the state of Connecticut, in New-England, in America, holden at Middletown, by adjournment, on the 18th day of December, 1776 : whereas commissioners of the four New-England states, have lately taken into consideration the importance of speedily raising and compleating their several quotas of the Continental Army, and have judged it reasonable to give a liberal encouragement to such as shall freely and speedily undertake in this service for the defence of themselves and country . (LLMC-digital (Series), 1777)
December 18, 1776 broadside issued by the Connecticut General Assembly which provided set bounties for enlisting into the Connecticut's eight battalions. Includes a proclamation by Governor Jonathan Trumbull calling on the citizens to join the cause to defend the country.